RANCANGAN RUANG PENGERING BERBASIS ERGONOMI MENURUNKAN KELUHAN MUSKULOSKELETAL PERAJIN IKAN - Susana, I Gede Bawa (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2016)
With  traditional fish drying process,  most possible can cause an unhealthy  working posture , such as a squatting action.   As a consequence , worker will suffer a  musculoskeletal disorders because of not  ergonomic tools and bad working posture. Without ergonomics  working  procedures was found that  the average of   musculoskeletal complaints after working is 52.25 ± 1.03. To solve this ccomplaints, a drying chamber based ergonomics design was built in order to reduce musculoskeletal disorders. Dimensions of the drying chamber were based on anthropometric data of fish craftsmen and the material of drying chamber was by the participatory method. Test was performed on 20 samples and the result showed that the mean rate of  musculoskeletal complaints after working is 38.30 ± 1.30. The ergonomic based design for drying camber application can reduce  the musculoskeletal complaints up to 26.7%.